Coaching education: The secret behind long-term program success - Dieffenbach, K. (Olympic & Paralympic Coach, 2019)
When athletes win championships and take home trophies, the credit for success often extends to the performance team - the strength and conditioning staff, the nutritionist and the athletic trainers. These are the people who assist the coaches in keeping the athletes healthy, strong and on track. But what about the coach? Who is responsible for helping the coach stay healthy, strong and on track? Coaching within a sports organization ranges from foundational and developmental sport to high performance. Exploring these systems and the people who prepare and support coaches is essential for developing impactful and successful programs. This is the first in a series of articles that will discuss and explore the essential role coaching education programs, coach educators and coach developers play in supporting long-term programmatic growth and positive outcomes.